لولا الامتناعية في القرآن الكريم -دراسة دلالية - حفوضة, رشيدة (University of Eloued جامعة الجزائر, 2020)
لحروف المعاني دورٌ وظيفيٌّ مهمٌّ في الدّلالاتِ المعنويَّةِ للجملةِ العربيّةِ؛ ويتوقّفُ فهمُ معاني القرآن الكريمِ، والتراثِ العربيِّ، شعرًا ونثرًا، على الإلمامِ بهذا الدّورِ الوظيفيِّ لكلِّ حرفٍ منها، في استعمالاتِه المختلفةِ. ولأجلِ هاتِهِ الأهمِّيَّةِ كان اختياري لحرفٍ مهمٍّ من تلك الحروفِ وهو (لولا) الامتناعيّةِ، وكان البحثُ بعنوانِ: (لولا) الامتناعيّةُ في القرآنِ الكريمِ دراسة دلاليّة، وهو يطرح الإجابة على الإشكال التالي: ماهي دلالاتُ (لولا الامتناعيّة) في القرآن الكريم؟ وقد توسّلتُ إلى معالجتِهِ؛ بتقريرِ مذاهبِ النحاة واللغويّيِنَ في إعرابها ودلالاتها، ثمَّ بتطبيقِ ذلك على مواضِعِها في القرآن الكريمِ؛ وكان التركيزُ في الجانبِ الدّلاليِّ على أحوالِ جوابِ(لولا) الامتناعيّةِ، وكانت النتائجُ كالتالي: أنَّه يجوز ذكرُ خبر(لولا) الامتناعيّة إذا كان كوناً مقيّدًا، وأحوالُ جوابُ(لولا) في القرآن الكرِيمِ: -أن يُذكرَ لغرضِ تعيِينِهِ؛ لعدم علم السامع بهِ، -أن يُذْكَرَ دونَ تعيِينِهِ؛ لغرضِ التهويلِ والتفخيمِ، -أن يُحْذَفَ لكونِهِ معلوماً من السِّياقِ، ولغرضِ التهويل و التفخيمٍ، -أن يُقَدَّمَ لغرضِ الاهتمامِ، ولتقْيِيدِ حُكْمِهِ المطلَقِ. والواجب أن نرجِّحَ استعمالَ القرآنِ، ونجعله الإِمامَ في دراساتنا والحكمَ عند اختلافاتِنا. The letters of meanings have an important functional role in the semantics of the Arabic sentence, Understanding the meanings of the Noble Qur’an and Arabic heritage, in poetry and prose, depends on familiarity with this functional role of each letter in its various uses Because of this importance, I chose significant letter from those letters, which is (had it not) for abstinence, and the research was titled: (If it were not for) abstinence in the Noble Qur’an is a semantic study, and it poses the answer to the following problem: What are the indications of (were it not for abstinence) in the Holy Qur’an? I used to treat it; By determining the doctrines of grammarians and linguists in their interpretation and significance, then applying that to their positions in the Holy Qur’an; The focus of the semantic aspect was on the states of the response (if not) of abstinence, and the results were as follows: that it is permissible to mention the news of (had it not) of refraining if it was a restricted universe, and the conditions of the answer (without) in the Noble Qur’an: - to be mentioned for the purpose of defining it; Because the listener is not aware of it, - to be mentioned without identifying it. For the purpose of exaggeration and exaggeration, - to be removed from the context, and for the purpose of intimidation and exaggeration, - to be presented for the purpose of concern, and to limit his absolute wisdom. It is necessary for us to favor the use of the Qur’an, make it the guidance in our studies and the judge when we differ.
مذكرة ماستر تخصص لغة ودراسات قرآنية
Keywords: حروف المعاني، لولا الامتناعيّة، الدلالة، القرآن الكريم.; The letters of meanings, Were it not for abstinence, Indication, The holy Qur’an.